2022
DOI: 10.3389/fphys.2022.843784
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Chronic Physical Exercise as a Treatment in the Development of Vitiligo

Abstract: Vitiligo is an autoimmune disease characterized by progressive skin depigmentation and the appearance of white patches throughout the body caused by significant apoptosis of epidermal melanocytes. Despite not causing any physical pain, vitiligo can originate several psychosocial disorders, drastically reducing patients’ quality of life. Emerging evidence has shown that vitiligo is associated with several genetic polymorphisms related to auto-reactivity from the immune system to melanocytes. Melanocytes from vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 125 publications
0
3
0
1
Order By: Relevance
“…A necessidade de lidar com problemas complexos levou ao surgimento de novas habilidades práticas, conhecimentos, atitudes e mudança comportamental. Essas mudanças são respostas à introdução de novas tecnologias e paradigmas na educação, de forma que os indivíduos estejam melhor preparados para lidar com as demandas da sociedade moderna (França;Dias;Borges, 2020).…”
Section: Aprofundamento Teórico E Prático Da Aprendizagem Colaborativ...unclassified
“…A necessidade de lidar com problemas complexos levou ao surgimento de novas habilidades práticas, conhecimentos, atitudes e mudança comportamental. Essas mudanças são respostas à introdução de novas tecnologias e paradigmas na educação, de forma que os indivíduos estejam melhor preparados para lidar com as demandas da sociedade moderna (França;Dias;Borges, 2020).…”
Section: Aprofundamento Teórico E Prático Da Aprendizagem Colaborativ...unclassified
“…Several studies have shown that overnutrition significantly increases the expression of senescence-associated REVIEW proteins, including the activity of p16, p53, p21, and SAβ-gal [102]. Exercise can inhibit the expression of SASPrelated genes and prevent the accumulation of senescent cells caused by overeating [103]. Mechanistically, exercise may reduce the metabolic and replicative stress of adipose tissue and limit the transition to senescence.…”
Section: Exercisementioning
confidence: 99%
“…Mechanistically, exercise may reduce the metabolic and replicative stress of adipose tissue and limit the transition to senescence. In addition, exercise may promote the elimination of senescent cells by the immune system [102,103].…”
Section: Exercisementioning
confidence: 99%
“…Damaged melanocytes release damage-associated molecular patterns, triggering an inflammatory gene expression response that ultimately leads to cell apoptosis. 3 .…”
Section: Introductionmentioning
confidence: 99%